Peningkatan kompetensi pengetahuan sosial-budaya bagi penulis dalam mendukung lahirnya karya sastra berbasis kearifan lokal - Ahmadin Ahmadin; Darman Manda; Rifal Rifal (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
This article is the result of community service that intends to provide the basis of understanding in order to improvethe ability of socio-cultural knowledge for writers for the birth of literary works based on local wisdom in Sulawesi Selatan. Thisprogram is considered very important given that the literary works produced by writers in this area are still very limited to makelocal wisdom as their contents. Whereas on the other hand local wisdom is an important part of the socio-cultural identity of thepeople which requires attention and preserves it. The method used in the process of increasing competency is to conduct trainingwith the following stages: (1) identifying the socio-cultural values of local communities that require socialization andpreservation, (2) collaborating with one of the author's organizations namely Ikatan Penulis Muslim Indonesia, (3) conductstraining on the potential of local noble values that can be used as writing material, and (4) records literary works based on localwisdom in the form of short story anthology. Thus, people can learn local wisdom through reading literature.